A note on approximation of blending type Bernstein-Schurer-Kantorovich operators with shape parameter α - Ayman-Mursaleen, Mohammad; Rao, Nadeem; Rani, Mamta; Kilicman, Adem; Al-Abied, Ahmed Ahmed Hussin Ali; Malik, Pradeep (Hindawi, 2023)
The objective of this paper is to construct univariate and bivariate blending type α-Schurer-Kantorovich operators depending on two parameters α∈[0,1] and ρ>0 to approximate a class of measurable functions on [0,1+q],q>0. We present some auxiliary results and obtain the rate of convergence of these operators. Next, we study the global and local approximation properties in terms of first- and second-order modulus of smoothness, weight functions, and by Peetre's K-functional in different function spaces. Moreover, we present some study on numerical and graphical analysis for our operators.